Ternary composite cathode system capable of recycling lithium supplement, preparation method and lithium ion battery
Patent Information
- Application Number
- CN202611441876.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0008]综上,现有补锂技术聚焦于首次容量补偿,未建立全循环周期的动态锂补偿机制,电芯循环中后期活性锂持续损耗,容量跳水快、循环寿命短;常规补锂剂在三元体系中副反应严重,存在锰溶出与产气问题,无法适配电池对产气膨胀的管控标准;此外,现有补锂技术量产难度大,设备改造成本高,与现有正极生产线兼容性差
1.区别一次性补锂方案,补锂剂可全周期动态补锂,全程可逆脱嵌锂,动态补偿循环过程的活性锂损耗,大幅提升电芯的循环寿命。
Smart Images

Figure FT_1 
Figure SMS_21
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a ternary composite cathode system with recyclable lithium replenishment, its preparation method, and lithium-ion batteries. Background Technology
[0002] High-nickel ternary materials have become the mainstream cathode material for power and pouch lithium-ion batteries due to their advantages of high specific capacity and high energy density. However, high-nickel ternary materials have problems such as high residual alkali on the surface and dissolution of transition metals during cycling, which continuously catalyze the decomposition of the electrolyte, causing the SEI film to continuously rupture and regenerate, irreversibly consuming the active lithium in the material system. As cycling progresses, the active lithium reserves in the cell continue to decrease, and the capacity usually decays rapidly after 1000 cycles, prematurely ending the cycle life.
[0003] To compensate for the loss of active lithium, existing technologies mainly include the following solutions: 1. Adding lithium oxalate or lithium sulfide to the positive electrode for one-time lithium replenishment. This releases lithium ions during the first charge, only compensating for the irreversible capacity of the initial formation. It cannot dynamically replenish the continuous lithium loss in the later stages of cycling. Moreover, the decomposition process is accompanied by the generation of a large amount of gas, making the cell prone to bulging failure, which is not suitable for mass production applications of ternary systems. 2. Using pre-lithiation technologies such as lithium strip composites for the negative electrode. This also only achieves one-time lithium replenishment and cannot repair the active lithium loss during cycling. Furthermore, the production of metallic lithium has high safety risks, poor process adaptability, and is difficult to mass-produce. 3. Mixing lithium-rich manganese-based materials into the positive electrode. Lithium-rich manganese-based materials have high initial irreversible capacity, significant voltage hysteresis, and severe gas generation at high temperatures. Directly mixing them into the ternary main phase will significantly reduce the cell's rate performance and storage performance, resulting in limited overall benefits.
[0004] CN202010030913.3 A lithium-replenishing additive, its preparation method, and a lithium-ion battery thereof. The lithium-replenishing additive uses a core-shell structure, with the core being a physical mixture of Li₂O and transition metal M (Mn / Fe / Co / Ni / Cu), and the outer shell being porous SiO₂. x A composite coating layer with carbon, 1-50 nm thick, enhances conductivity through the carbon layer and SiO2. x Suppressing the dissolution of the core metal enables one-time lithium replenishment on the positive electrode side.
[0005] CN202511306143.X A lithium replenishing additive, its preparation method, and a battery containing the lithium replenishing additive are disclosed. The lithium replenishing additive used is copper-doped modified Li₂NiO₂ powder with the chemical formula Li₂NiO₂. 1-x Cu x O2 (x=0.1~0.5) weakens the Li-O bond energy through copper doping, improving delithiation kinetics and conductivity. This lithium replenisher is specifically adapted to the lithium iron phosphate system, which can reduce delithiation polarization, improve the first lithium replenishment efficiency, and improve battery cycle performance.
[0006] CN202210908451.X A method for preparing and applying a positive electrode lithium supplementation additive, employing a carbon-coated silicate-based nano-lithium supplementation agent, the material system being carbon-coated Li... x M y O nanoparticles (M is Si / Ge / Sn) have a theoretical lithium replenishment capacity of up to 1191mAh / g and support multi-element doping modification. This lithium replenishment agent can be used for coating on the positive electrode side of the separator, mixing of positive electrode slurry, and secondary coating on the surface of the electrode. Its core function is to build a dual ion and electron conduction network, give full play to capacity advantages, and improve the specific capacity of the first charge.
[0007] Existing patented lithium replenishment mechanisms are limited to one-time replenishment, only compensating for the initial loss of active lithium in the SEI film. They cannot continuously replenish lithium consumed by side reactions during cycling, thus failing to effectively improve capacity decay over long cycles. Electrochemical compatibility is insufficient, with generally high delithiation potentials. These technologies either only adapt to low-voltage lithium iron phosphate systems or require increasing the upper charging voltage to achieve capacity, exacerbating electrolyte side reactions and battery gas production. Cyclic structural stability is poor; the core is prone to pulverization, the coating layer is easily broken, and the structure collapses after delithiation. Transition metal dissolution and volume expansion problems gradually worsen with cycling. There are shortcomings in mass production implementation, including the use of hazardous raw materials, high environmental requirements, or the need for additional production line processes, resulting in high mass production costs and significant challenges in process control.
[0008] In summary, existing lithium replenishment technologies focus on initial capacity compensation and have not established a dynamic lithium compensation mechanism for the entire cycle. Active lithium is continuously depleted in the later stages of cell cycling, resulting in rapid capacity drop and short cycle life. Conventional lithium replenishment agents cause serious side reactions in ternary systems, leading to manganese dissolution and gas generation issues, and cannot be adapted to the battery's control standards for gas expansion. In addition, existing lithium replenishment technologies are difficult to mass-produce, have high equipment modification costs, and poor compatibility with existing cathode production lines. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide a ternary composite cathode system with recyclable lithium replenishment, its preparation method, and a lithium-ion battery.
[0010] To solve the above technical problems, the present invention adopts the concept of "reversible lithium storage", which achieves full-cycle dynamic lithium compensation by combining a core-shell structured cyclic lithium replenishment additive with ternary materials. The specific technical solution is as follows: A cyclic lithium replenishment ternary composite cathode system, comprising a high-nickel ternary cathode material, a cyclic lithium replenishment additive, a conductive agent and a binder. The recyclable lithium replenishment additive has a core-shell structure, with its core being lithium-rich spinel lithium manganese oxide, chemically represented as Li. 1+x Mn₂O₄, where x = 0.1 0.3; the core surface is covered with a thickness of 2 A 5 nm thin layer of lithium aluminum oxide (LiAlO2) or aluminum oxide (Al2O3); the charge / discharge potential range of the lithium-rich spinel lithium manganese oxide is 3.0 nm. 4.3V, which matches the charge and discharge range of the high-nickel ternary cathode material, has reversible lithium insertion / extraction capability, and is used to dynamically compensate for the active lithium loss of the ternary cathode system throughout the entire cycle.
[0011] Furthermore, based on the total mass percentage of the ternary composite cathode system, the content of the high-nickel ternary cathode material is 92%. 96%, and the content of the recyclable lithium supplement additive is 1%. 5%, the content of the conductive agent is 1.5%. 2.5%, the content of the adhesive is 1.5%. 2.5%.
[0012] Preferably, the content of the recyclable lithium supplement additive is 2%. 3%.
[0013] Furthermore, the high-nickel ternary cathode material is a single-crystal NCM7, 8, or 9 series ternary material; the conductive agent is one or more combinations of conductive carbon black, carbon nanotubes, and graphene; and the binder is polyvinylidene fluoride.
[0014] Furthermore, the material of the thin layer is lithium aluminum oxide (LiAlO2), and x = 0.2 in the lithium-rich spinel lithium manganese oxide.
[0015] A method for preparing a ternary composite cathode system as described above includes the following steps: (1) Preparation of coated recyclable lithium replenishment additive: lithium-rich spinel Li was synthesized by high-temperature solid-state method. 1+x The Mn2O4 substrate is coated with the 2O4 material via liquid phase coating or atomic layer deposition. The recyclable lithium replenishing additive is obtained by sintering, crushing, and sieving a 5nm lithium aluminum oxide LiAlO2 or aluminum oxide Al2O3 coating layer. (2) Pre-dispersion treatment: The recyclable lithium additive and a portion of the conductive agent are added to NMP solvent at a mass ratio of 1:1 and stirred at high speed for 30 minutes. 60 minutes to prepare a uniform pre-dispersed slurry; (3) Positive electrode slurry preparation: Add the remaining conductive agent, the high-nickel ternary positive electrode material, and the PVDF binder to the pre-dispersed slurry, and stir under low-speed vacuum for 2 hours. After 4 hours, adjust the slurry solids content to 65%. 75%; (4) Coating and molding: The positive electrode slurry obtained in step (3) is coated on the aluminum foil current collector, and after being dried in a segmented gradient, it is cold-pressed to the designed compaction density to obtain a composite positive electrode sheet.
[0016] Furthermore, the high-speed stirring speed in step (2) is 2000. 3000rpm, the low-speed vacuum stirring speed in step (3) is 800rpm, and the stirring temperature is room temperature.
[0017] A lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises the above-mentioned cyclically replenishable ternary composite positive electrode system. The electrolyte is a system of carbonate mixed solvent and lithium hexafluorophosphate, and 1% of lithium salt is added to the electrolyte. 2% fluoroethylene carbonate (FEC) and 0.5% 1% borate ester film-forming additives; The FEC and borate ester film-forming additives are used to form a dense and stable SEI film on the negative electrode to reduce the basic consumption of active lithium from the source, and form a two-way synergistic effect of "reducing loss + replenishing reserves" with the recyclable lithium replenishment additive.
[0018] Furthermore, the negative electrode sheet includes an artificial graphite negative electrode or a silicon-carbon negative electrode; the separator is a polyolefin separator.
[0019] Furthermore, the borate film-forming additive is tripropyl borate.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. Unlike one-time lithium replenishment solutions, lithium replenishment agents can dynamically replenish lithium throughout the entire cycle, and can reversibly insert and extract lithium throughout the entire process, dynamically compensating for the loss of active lithium during the cycle, and significantly improving the cycle life of the battery cell.
[0021] 2. The ultra-thin coating layer effectively isolates the side reaction between the ternary residual alkali and the lithium replenishing agent, and inhibits the dissolution of manganese ions. Compared with the lithium replenishing agent without the coating layer, it effectively reduces the probability of high-temperature gas generation and meets the usage requirements of lithium-ion batteries.
[0022] 3. The initial efficiency is improved by about 3%, which directly increases the effective capacity of the cell. Furthermore, the spinel phase three-dimensional lithium-ion channel ensures high-rate performance, and the battery's high-rate discharge capability is not lost.
[0023] 4. Strong mass production compatibility: only lithium supplementation agent is added in the positive electrode homogenization process, without the need for new equipment, and it is fully compatible with the existing electrode production line; the increase in material cost is much lower than that of the negative electrode pre-lithiation scheme, and there is no safety production risk. Attached Figure Description
[0024] Figure 1This is the charge-discharge curve of the lithium supplementation additive in Example 2 of the present invention. Detailed Implementation
[0025] To make the technical problems, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0026] This invention provides a ternary composite cathode system with recyclable lithium replenishment, comprising a ternary cathode material, a recyclable lithium replenishment additive, a conductive agent, and a binder.
[0027] The recyclable lithium replenishment additive has a core-shell structure: the core is a lithium-rich spinel lithium manganese oxide (Li). 1+x Mn2O4 (x=0.1~0.3) has a charge / discharge potential range of 3.0~4.3V, which is perfectly matched with the charge / discharge range of the ternary main material, and has a stable reversible lithium insertion / extraction capability; the surface is coated with a 2~5nm thick lithium aluminum oxide (LiAlO2) or aluminum oxide (Al2O3) thin layer, which isolates the strong alkaline environment of the high nickel ternary material and inhibits the dissolution of manganese ions and side reactions of the electrolyte.
[0028] Based on the total weight percentage of the cathode material, the preferred content of each component is as follows: 92%~96% for high-nickel ternary cathode material, 1%~5% for recyclable lithium replenishment additive, 1.5%~2.5% for conductive agent, and 1.5%~2.5% for binder; among which, the optimal addition amount of lithium replenishment additive is 2%~3%, which balances lithium replenishment effect and energy density.
[0029] Furthermore, the high-nickel ternary cathode material is a single-crystal NCM7, 8, or 9 series ternary material; the conductive agent is one or more combinations of conductive carbon black, carbon nanotubes, and graphene; and the binder is polyvinylidene fluoride.
[0030] The preparation method of the above-mentioned ternary composite cathode system includes the following steps: (1) Preparation of coated recyclable lithium replenishment additive: lithium-rich spinel Li was synthesized by high-temperature solid-state method. 1+x The target lithium supplement additive is obtained by depositing a 2-5 nm LiAlO2 / Al2O3 coating layer on the surface of the Mn2O4 matrix through liquid phase coating or atomic layer deposition, followed by sintering, crushing and sieving. (2) Pre-dispersion treatment: Add the recyclable lithium supplementation additive and the conductive agent to NMP solvent at a mass ratio of 1:1, stir at high speed for 30~60min to make a uniform pre-dispersion slurry, so as to avoid the agglomeration of additives at low addition amount; (3) Positive electrode homogenization: Add high-nickel ternary positive electrode material and polyvinylidene fluoride binder to the pre-dispersed slurry, stir at low speed under vacuum for 2-4 hours, adjust the solid content of the slurry to 65%-75%, and the viscosity meets the coating requirements; (4) Coating and molding: The positive electrode slurry is coated on the aluminum foil current collector, dried in a segmented gradient, and then cold-pressed to the designed compaction density to obtain the composite positive electrode sheet.
[0031] The present invention also provides a lithium-ion battery comprising the above-mentioned composite positive electrode, and further comprising a negative electrode (artificial graphite or silicon-carbon negative electrode), a polyolefin separator, and an electrolyte.
[0032] The electrolyte is a carbonate mixed solvent + lithium hexafluorophosphate system, with 1%~2% fluoroethylene carbonate (FEC) and 0.5%~1% borate film-forming additives added. It preferentially forms a dense and stable SEI film on the negative electrode, reducing the basic consumption of active lithium from the source, and forming a two-way synergistic effect of "reducing loss + replenishing reserves" with the lithium replenishing agent.
[0033] Example 1 This embodiment uses uncoated Li 1.2 Lithium-rich spinel Mn2O4 was added to the NCM811 cathode system as a lithium supplement additive at a ratio of 2% of the total cathode mass.
[0034] 1) Preparation of lithium-rich spinel lithium supplement: Li-rich spinel was synthesized using a high-temperature solid-state method. 1.2 Lithium-rich spinel powder (Mn2O4): Lithium carbonate and electrolytic manganese dioxide were accurately weighed according to the Li / Mn molar ratio of 1.2:2 and added to a planetary ball mill. The mixture was ball-milled at 300 rpm for 6 hours until homogeneous. The mixed powder was transferred to an alumina crucible and placed in a high-temperature box furnace with an air atmosphere. The temperature was raised to 850°C at a heating rate of 5°C / min and sintered at that temperature for 12 hours. After natural cooling in the furnace, the powder was crushed and sieved to obtain lithium-rich spinel lithium supplement powder with a D50 of 1.8 μm.
[0035] 2) Preparation of composite positive electrode sheet: Weigh 94% of single-crystal NCM811 positive electrode material, 2% of the above-mentioned lithium-rich spinel lithium supplementer, 2% of conductive carbon black, and 2% of PVDF binder by mass percentage. First, completely dissolve PVDF in NMP solvent to prepare a PVDF slurry with a mass fraction of 8%. Add conductive carbon black and lithium supplementer powder to the slurry and disperse at high speed of 2000 rpm for 30 min until uniform dispersion. Then add single-crystal NCM811 material and stir at low speed of 800 rpm for 3 h under vacuum of -0.095 MPa and room temperature. Adjust the solid content of the slurry to 73% and measure the viscosity of the slurry at 25℃ to be 6500 mPa. The positive electrode slurry was uniformly coated on both sides of a 12μm thick smooth aluminum foil using a four-stage gradient drying process, with the coating speed controlled at 1.2m / min. After drying, it was cold-pressed by a roller press to a compaction density of 3.3g / cm³. 3 The electrodes are cut into specified sizes, and the areal density of the electrodes is controlled to be 22.0 ± 0.5 mg / cm³. 2 .
[0036] 3) Preparation of negative electrode sheet: Weigh 95% artificial graphite negative electrode material, 1.5% conductive carbon black, 1.5% sodium carboxymethyl cellulose, and 2% styrene-butadiene rubber by mass percentage; using deionized water as the dispersion solvent, first dissolve CMC to prepare a glue solution, add conductive carbon black and artificial graphite and disperse evenly, and finally add SBR and stir to prepare negative electrode slurry; coat the negative electrode slurry on both sides of 8μ double-sided bright copper foil, dry and cold press to prepare negative electrode sheet, control the compaction density to be 1.65g / cm², and design the cell N / P ratio to be 1.15.
[0037] 4) Lithium-ion battery preparation: A soft-pack cell with a rated capacity of 50Ah is prepared using a stacking process. The separator is a 9μm thick single-sided ceramic-coated polypropylene separator. After the electrode and separator are stacked, they are encapsulated in aluminum-plastic film using a top-side sealing machine. Electrolyte is injected with an injection coefficient of 2.2g / Ah. The electrolyte formula is: electrolyte base liquid + 1% FEC by mass. After standing at room temperature for 24 hours, the formation process is carried out: first, it is charged to 3.0V with a constant current of 0.05C, and then charged to 3.8V with a constant current of 0.2C. After formation, degassing and secondary encapsulation are completed. Finally, the finished cell is obtained through a capacity grading process.
[0038] Example 2 This embodiment uses a core-shell structure lithium supplementation additive with a LiAlO2 coating layer thickness of 3nm, added at a ratio of 2% of the total mass of the positive electrode, and combined with a composite electrolyte of FEC and tripropyl borate. This embodiment is a preferred embodiment of the present invention.
[0039] 1) Preparation of core-shell structured recyclable lithium-replenishing additive: First, a lithium-rich spinel matrix was prepared using the same synthesis process as in Example 1, resulting in Li1.2Mn2O4 lithium-rich spinel powder with D50 = 1.8 μm. Then, a LiAlO2 protective layer was coated onto the lithium-rich spinel powder using a liquid-phase method. Lithium-rich spinel powder was dispersed in deionized water to prepare a 10% (w / w) suspension. The suspension was kept at a constant temperature of 60°C in a water bath with continuous stirring. The feed amount was calculated based on a target coating thickness of 3 nm. Aluminum nitrate and lithium carbonate were accurately weighed, dissolved, and slowly added dropwise to the suspension. Simultaneously, 0.5 mol / L ammonia was added dropwise to adjust the pH of the system to 8.5. After the addition was completed, the mixture was stirred at a constant speed for 2 hours and allowed to stand for 4 hours. Subsequently, the mixture was filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 12 hours. The dried powder was then transferred to an air atmosphere furnace and heated to 500°C at a rate of 5°C / min, and sintered at that temperature for 4 hours. After cooling in the furnace, the powder was crushed and sieved to obtain a LiAlO2-coated recyclable lithium replenishment additive.
[0040] TEM characterization showed that the thickness of the lithium-replenishing additive coating layer prepared in this embodiment was 2.8–3.2 nm, with an average thickness of approximately 3 nm. Coin cell testing showed that the reversible specific capacity of this additive was 158 mAh / g within the voltage range of 3.0–4.3 V. See [link / reference]. Figure 1 . 2) Preparation of composite positive electrode sheet: Weigh 94% of the single-crystal NCM811 positive electrode material, 2% of the above-mentioned coated lithium-supplementing additive, 2% of conductive carbon black, and 2% of polyvinylidene fluoride binder by mass percentage. A pre-dispersion process is used to avoid agglomeration of powder with low additive amounts: First, the lithium-supplementing additive and a portion of the conductive carbon black are added to NMP solvent at a mass ratio of 1:1 and dispersed at a high speed of 3000 rpm for 45 min to prepare a uniform pre-dispersion slurry; then, add the remaining conductive carbon black, PVDF adhesive, and single-crystal NCM811 material to the pre-dispersion slurry, and stir at a low speed of 800 rpm for 3 h under vacuum conditions of -0.095 MPa and 25℃; adjust the solid content of the slurry to 70.5%, and measure the slurry viscosity at 25℃ to be 6800 mPa. The coating, drying, cold pressing, and electrode cutting processes were the same as in Example 1, controlling the electrode areal density to be 22.0 ± 0.5 mg / cm³. 2 The compacted density is 3.4 g / cm³. 3 .
[0041] 3) Preparation of negative electrode sheet: The negative electrode slurry formulation, preparation process and N / P ratio design are the same as in Example 1.
[0042] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 1; the electrolyte formula is adjusted to: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 1.
[0043] Example 3 This embodiment verifies the cell performance when the lithium supplementation additive content is increased to 4%. The coating process and electrolyte formulation are the same as in Example 2.
[0044] 1) Preparation of core-shell structured recyclable lithium replenishment additive: Using the same liquid phase coating process as in Example 2, a recyclable lithium replenishment additive with an average LiAlO2 coating layer thickness of 3 nm was prepared.
[0045] 2) Preparation of composite positive electrode sheet: Weigh 92% single-crystal NCM811 positive electrode material, 4% of the above-mentioned coated lithium-supplementing additive, 2% conductive carbon black, and 2% polyvinylidene fluoride binder by mass percentage. The slurry is prepared using the same dispersion process as in Example 2. After pre-dispersing the lithium-supplementing additive and conductive carbon black, the remaining raw materials are added and vacuum stirred. The solid content of the slurry is adjusted to 72%, and the viscosity of the slurry at 25°C is 7100 mPa. The coating, drying, cold pressing, and cutting process parameters were the same as in Example 2, and the electrode surface density was controlled at 22.0 ± 0.5 mg / cm². 2 Compacted density 3.4 g / cm³ 3 .
[0046] 3) Preparation of negative electrode sheet: The negative electrode slurry formulation, preparation process and N / P ratio design are the same as in Example 2.
[0047] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0048] Example 4 This embodiment verifies the cell performance when the LiAlO2 coating thickness is increased to 5nm. The amount of lithium replenishing agent and the electrolyte formulation are the same as in Example 2.
[0049] 1) Preparation of core-shell structure recyclable lithium replenishment additive: The lithium-rich spinel matrix was prepared using the same process as in Example 2. In the liquid phase coating process, the amount of aluminum nitrate and lithium carbonate was increased proportionally to the target coating thickness of 5nm. The remaining pH control, stirring, aging, drying and sintering process parameters were completely consistent with those in Example 2. A recyclable lithium replenishment additive with an average LiAlO2 coating thickness of 5nm was obtained.
[0050] 2) Preparation of composite positive electrode sheet: The positive electrode formulation, pre-dispersion slurry process, and coating and cold pressing parameters are all the same as in Example 2. The electrode sheet areal density is 22.0 ± 0.5 mg / cm³. 2 Compacted density 3.4 g / cm³ 3 .
[0051] 3) Preparation of negative electrode sheet: The negative electrode slurry formulation, preparation process and N / P ratio design are the same as in Example 2.
[0052] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0053] Example 5 This embodiment verifies the compatibility of the proposed lithium supplementation additive in the NCM 9-series system. 1) Preparation of core-shell structured recyclable lithium replenishment additive: Using the same process as in Example 2, a recyclable lithium replenishment additive with an average LiAlO2 coating thickness of 3 nm was prepared.
[0054] 2) Preparation of composite positive electrode sheet: Weigh 94% single-crystal NCM 9-series positive electrode material, 2% of the above-mentioned coated lithium-supplementing additive, 2% conductive carbon black, and 2% polyvinylidene fluoride binder by mass percentage. The slurry is prepared using the same dispersion process as in Example 2. After pre-dispersing the lithium-supplementing additive and conductive carbon black, the remaining raw materials are added and vacuum stirred. The solid content of the slurry is adjusted to 72%, and the viscosity of the slurry at 25°C is 7000 mPa. The coating, drying, cold pressing, and cutting process parameters were the same as in Example 2, and the electrode surface density was controlled at 22.0 ± 0.5 mg / cm². 2 The compacted density is 3.35 g / cm³. 3 .
[0055] 3) Preparation of negative electrode sheet: The negative electrode slurry formula and preparation process are the same as in Example 2. The NP ratio is designed to be 1.15, and the electrode sheet thickness is adjusted accordingly.
[0056] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0057] Example 6 This embodiment verifies the lithium replenishment effect when the lithium-rich spinel x=0.1. The coating thickness, addition amount, and electrolyte formula are the same as in Example 2.
[0058] 1) Preparation of lithium-rich spinel lithium supplement: Li-rich spinel was synthesized using a high-temperature solid-state method. 1.1 Lithium-rich spinel powder (Mn2O4): Lithium carbonate and electrolytic manganese dioxide were accurately weighed according to a Li / Mn molar ratio of 1.1:2 and added to a planetary ball mill. The mixture was ball-milled at 300 rpm for 6 hours until homogeneous. The powder mixture was then transferred to an alumina crucible and placed in a high-temperature box furnace under air atmosphere. The temperature was increased to 850°C at a rate of 5°C / min and sintered at that temperature for 12 hours. After natural cooling in the furnace, the powder was crushed and sieved to obtain lithium-rich spinel powder with a D50 of 1.8 μm. Then, a LiAlO2 protective layer was coated onto the lithium-rich spinel powder using a liquid-phase method. Lithium-rich spinel powder was dispersed in deionized water to prepare a 10% (w / w) suspension. The suspension was kept at a constant temperature of 60°C in a water bath with continuous stirring. The feed amount was calculated based on a target coating thickness of 3 nm. Aluminum nitrate and lithium carbonate were accurately weighed, dissolved, and slowly added dropwise to the suspension. Simultaneously, 0.5 mol / L ammonia was added dropwise to adjust the pH of the system to 8.5. After the addition was completed, the mixture was stirred at a constant speed for 2 hours and allowed to stand for 4 hours. Subsequently, the mixture was filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 12 hours. The dried powder was then transferred to an air atmosphere furnace and heated to 500°C at a rate of 5°C / min, and sintered at that temperature for 4 hours. After cooling in the furnace, the powder was crushed and sieved to obtain a LiAlO2-coated recyclable lithium replenishment additive.
[0059] According to button cell testing, the reversible specific capacity of this additive is 145mAh / g in the voltage range of 3.0~4.3V.
[0060] 2) Preparation of composite positive electrode sheet: The positive electrode formulation, pre-dispersion slurry process, and coating and cold pressing parameters are all the same as in Example 2. The electrode sheet areal density is 22.0 ± 0.5 mg / cm³. 2 Compacted density 3.4 g / cm³ 3 .
[0061] 3) Preparation of negative electrode sheet: The negative electrode slurry formula and preparation process are the same as in Example 2. The NP ratio is designed to be 1.15, and the electrode sheet thickness is adjusted accordingly.
[0062] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0063] Example 7 This embodiment verifies the lithium replenishment effect when the lithium-rich spinel x=0.3. The coating thickness, addition amount, and electrolyte formula are the same as in Example 2.
[0064] 1) Preparation of lithium-rich spinel lithium supplement: Li-rich spinel was synthesized using a high-temperature solid-state method. 1.1 Lithium-rich spinel powder (Mn2O4): Lithium carbonate and electrolytic manganese dioxide were accurately weighed according to a Li / Mn molar ratio of 1.3:2 and added to a planetary ball mill. The mixture was ball-milled at 300 rpm for 6 hours until homogeneous. The powder mixture was then transferred to an alumina crucible and placed in a high-temperature box furnace under air atmosphere. The temperature was increased to 850°C at a rate of 5°C / min and sintered at that temperature for 12 hours. After natural cooling in the furnace, the powder was crushed and sieved to obtain lithium-rich spinel powder with a D50 of 1.8 μm. Then, a LiAlO2 protective layer was coated onto the lithium-rich spinel powder using a liquid-phase method. Lithium-rich spinel powder was dispersed in deionized water to prepare a 10% (w / w) suspension. The suspension was kept at a constant temperature of 60°C in a water bath with continuous stirring. The feed amount was calculated based on a target coating thickness of 3 nm. Aluminum nitrate and lithium carbonate were accurately weighed, dissolved, and slowly added dropwise to the suspension. Simultaneously, 0.5 mol / L ammonia was added dropwise to adjust the pH of the system to 8.5. After the addition was completed, the mixture was stirred at a constant speed for 2 hours and allowed to stand for 4 hours. Subsequently, the mixture was filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 12 hours. The dried powder was then transferred to an air atmosphere furnace and heated to 500°C at a rate of 5°C / min, and sintered at that temperature for 4 hours. After cooling in the furnace, the powder was crushed and sieved to obtain a LiAlO2-coated recyclable lithium replenishment additive.
[0065] According to button cell testing, the reversible specific capacity of this additive is 166mAh / g in the voltage range of 3.0~4.3V.
[0066] 2) Preparation of composite positive electrode sheet: The positive electrode formulation, pre-dispersion slurry process, and coating and cold pressing parameters are all the same as in Example 2. The electrode sheet areal density is 22.0 ± 0.5 mg / cm³. 2 Compacted density 3.4 g / cm³ 3 .
[0067] 3) Preparation of negative electrode sheet: The negative electrode slurry formula and preparation process are the same as in Example 2. The NP ratio is designed to be 1.15, and the electrode sheet thickness is adjusted accordingly.
[0068] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0069] Example 8 This embodiment verifies the cell performance when the LiAlO2 coating thickness is 2nm. The lithium-rich spinel x-value, additive content, and electrolyte formulation are consistent with those in Example 2.
[0070] 1) Preparation of core-shell structure recyclable lithium replenishment additive: The lithium-rich spinel matrix was prepared using the same process as in Example 2. In the liquid phase coating process, the amount of aluminum nitrate and lithium carbonate was increased proportionally to the target coating thickness of 5nm. The remaining pH control, stirring, aging, drying and sintering process parameters were completely consistent with those in Example 2. A recyclable lithium replenishment additive with an average LiAlO2 coating thickness of 5nm was obtained.
[0071] 2) Preparation of composite positive electrode sheet: The positive electrode formulation, pre-dispersion slurry process, and coating and cold pressing parameters are all the same as in Example 2. The electrode sheet areal density is 22.0 ± 0.5 mg / cm³. 2 Compacted density 3.4 g / cm³ 3 .
[0072] 3) Preparation of negative electrode sheet: The negative electrode slurry formulation, preparation process and N / P ratio design are the same as in Example 2.
[0073] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0074] Comparative Example 1 This comparative example is a conventional monocrystalline NCM811 pouch cell system without lithium replenishment, used to compare its performance with the above embodiments.
[0075] Weigh out 96% single-crystal NCM811 cathode material, 2% conductive carbon black, and 2% PVDF binder by mass percentage.
[0076] 1) Preparation of positive electrode sheet: First, PVDF was completely dissolved in NMP solvent to prepare a PVDF solution with a mass fraction of 8%; conductive carbon black was added to the solution and dispersed at a high speed of 2000 rpm for 30 min; then, single crystal NCM811 main material was added, and the solution was stirred at a low speed of 800 rpm for 3 h under vacuum of -0.095 MPa and room temperature; the solid content of the slurry was adjusted to 73%, and the viscosity of the slurry at 25℃ was measured to be 6500 mPa. The coating, four-stage gradient drying, cold pressing, and cutting processes were the same as in Example 1, controlling the electrode surface density to be 22.0 ± 0.5 mg / cm³. 2 The compacted density is 3.4 g / cm³. 3 .
[0077] 2) Preparation of negative electrode sheet: The negative electrode slurry formulation, preparation process and NP ratio are completely consistent with those in Example 1.
[0078] 3) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0079] Comparative Example 2 This comparative example verifies the battery performance when the coating thickness is 1 nm. Except for the coating thickness, the other parameters are the same as in Example 2.
[0080] 1) Preparation of lithium-rich spinel lithium supplement: The preparation process of the lithium-rich spinel matrix is the same as in Example 2. Then, the lithium-rich spinel powder is coated with a LiAlO2 protective layer using a liquid phase method. The lithium-rich spinel powder is dispersed in deionized water to prepare a 10% (w / w) suspension. The suspension is kept at a constant temperature of 60°C in a water bath with continuous stirring. The feed amount is calculated based on the target coating thickness of 1 nm. Aluminum nitrate and lithium carbonate are accurately weighed, dissolved, and slowly added dropwise to the suspension. Simultaneously, 0.5 mol / L ammonia is added dropwise to adjust the pH of the system to 8.5. After the addition is completed, the mixture is stirred at a uniform speed for 2 hours and allowed to stand for 4 hours. Subsequently, the mixture is filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 12 hours. The dried powder is then transferred to an air atmosphere furnace and heated to 500°C at a rate of 5°C / min, and sintered at that temperature for 4 hours. After cooling in the furnace, the powder is crushed and sieved to obtain a LiAlO2-coated recyclable lithium supplement additive.
[0081] 2) Preparation of composite positive electrode sheet: The positive electrode formulation, pre-dispersion slurry process, and coating and cold pressing parameters are all the same as in Example 2. The electrode sheet areal density is 22.0 ± 0.5 mg / cm³. 2 Compacted density 3.4 g / cm³ 3 .
[0082] 3) Preparation of negative electrode sheet: The negative electrode slurry formula and preparation process are the same as in Example 2. The NP ratio is designed to be 1.15, and the electrode sheet thickness is adjusted accordingly.
[0083] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0084] Comparative Example 3 This comparative example verifies the battery performance when the coating thickness is 6nm. Except for the coating thickness, the other parameters are the same as in Example 2.
[0085] 1) Preparation of lithium-rich spinel lithium supplement: The preparation process of the lithium-rich spinel matrix is the same as in Example 2. Then, the lithium-rich spinel powder is coated with a LiAlO2 protective layer using a liquid phase method. The lithium-rich spinel powder is dispersed in deionized water to prepare a 10% (w / w) suspension. The suspension is kept at a constant temperature of 60°C in a water bath with continuous stirring. The feed amount is calculated according to the target coating thickness of 6nm. Aluminum nitrate and lithium carbonate are accurately weighed, dissolved, and slowly added dropwise to the suspension. Simultaneously, 0.5mol / L ammonia water is added dropwise to adjust the pH of the system to 8.5. After the addition is completed, the mixture is stirred at a uniform speed for 2 hours and allowed to stand for 4 hours. Then, it is filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 12 hours. The dried powder is transferred to an air atmosphere furnace and heated to 500°C at a rate of 5°C / min. It is then sintered at this temperature for 4 hours. After cooling in the furnace, the powder is crushed and sieved to obtain a LiAlO2-coated recyclable lithium supplement additive.
[0086] 2) Preparation of composite positive electrode sheet: The positive electrode formulation, pre-dispersion slurry process, and coating and cold pressing parameters are all the same as in Example 2. The electrode sheet areal density is 22.0 ± 0.5 mg / cm³. 2 Compacted density 3.4 g / cm³ 3 .
[0087] 3) Preparation of negative electrode sheet: The negative electrode slurry formula and preparation process are the same as in Example 2. The NP ratio is designed to be 1.15, and the electrode sheet thickness is adjusted accordingly.
[0088] 4) Lithium-ion battery preparation: The negative electrode, separator, stacking, and top-side sealing processes are the same as in Example 2; the electrolyte formula is: electrolyte base liquid + 1.5% FEC by mass + 0.8% tripropyl borate by mass; the injection coefficient, standing, formation, secondary packaging, and capacity testing processes are all the same as in Example 2.
[0089] The batteries fabricated in each embodiment and the comparative example were tested as follows: First charge-discharge test: At room temperature of 25℃, charge at a constant current of 0.1C to 4.25V, then switch to constant voltage charging until the current drops to 0.05C cutoff; after standing for 30 minutes, discharge at a constant current of 0.1C to 2.8V, and calculate the first discharge specific capacity and the first coulombic efficiency.
[0090] Cyclic performance test: At 25℃, the battery cell was charged and discharged at a constant current of 1C with a voltage range of 2.8~4.25V. The cell discharge capacity was recorded once every 100 cycles, and the capacity retention rate was calculated after 1000 cycles and 1500 cycles.
[0091] High-temperature gas generation test: The battery cell was placed in a 60℃ environment for 30 days with a full charge. The volume change of the battery cell before and after storage was measured by the water displacement method, and the volume gas generation rate was calculated.
[0092] Rate performance test: Constant current discharge was performed at 0.2C, 1C and 3C respectively. The capacity retention rate at different rates was calculated based on the 0.2C discharge capacity.
[0093] The battery performance corresponding to each embodiment is shown in the table below:
[0094] Test Result Analysis: 1. Spinel matrix (Li 1+x Verification of the reasonableness of the value range of Mn2O4(x) A comparison of the cycling performance of Examples 6 (x=0.1), 2 (x=0.2), and 7 (x=0.3) with the control example without lithium replenishment shows that the 1500-cycle capacity retention rates are 77.9%, 82.1%, and 79.7%, respectively, representing improvements of 16.7, 20.9, and 18.5 percentage points compared to Control Example 1 (the conventional system without lithium replenishment, 61.2%). Significant improvements in cycle life are observed across the entire range. At x=0.1, the exchangeable lithium content in the spinel lattice is relatively low, resulting in limited lithium capacity and insufficient dynamic lithium replenishment reserves during long-cycle cycles. The initial efficiency and cycle capacity retention rates are slightly lower than the optimal level at x=0.2, but still significantly better than the system without lithium replenishment. At x=0.3, the spinel exhibits higher initial delithiation capacity and a significant improvement in initial efficiency; however, excessive lithium insertion reduces the structural stability of the spinel lattice, and the risk of manganese dissolution increases slightly during long-cycle cycles. Therefore, the 1500-cycle capacity retention rate is slightly lower than that of the x=0.2 example, but still at an excellent level. The above indicates that x = 0.1~0.3 is the optimal operating range, which can balance lithium storage capacity, structural stability, and long-cycle lithium replenishment effect. The reversible lithium replenishment effect of this invention can be stably achieved throughout the entire range.
[0095] 2. Verification of the rationality of the coating thickness A comparison of Examples 8, 2, and 4 with Comparative Examples 2 and 3 (coating thicknesses of 2nm, 3nm, 5nm, 1nm, and 6nm, respectively) reveals the following: A coating thickness of 1nm is insufficient to effectively isolate the spinel from the erosion of high-nickel residual alkali and electrolyte, resulting in inadequate manganese dissolution suppression. The 1500-cycle capacity retention is only 75.5%, with limited improvement in cycle life, and the high-temperature gas generation rate is only slightly lower than that of Example 1 without coating. A coating thickness of 2-5nm effectively isolates side reactions, suppresses manganese dissolution and gas generation, without significantly hindering lithium-ion conduction. Rate performance remains unaffected, with a 1500-cycle capacity retention of over 79% and a significant improvement in cycle life. A coating thickness of 6nm is too large, significantly increasing ion conduction resistance. The 3C rate capacity retention drops to 89.8%, and both initial coulombic efficiency and capacity retention decline. Increased polarization leads to incomplete lithium insertion / extraction during long cycles, accelerating the loss of active lithium. The above indicates that a coating thickness of 2-5 nm is the optimal range, balancing interface protection and ion conduction performance.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A ternary composite cathode system with recyclable lithium replenishment, comprising a high-nickel ternary cathode material, a recyclable lithium replenishment additive, a conductive agent, and a binder, characterized in that, The recyclable lithium replenishment additive has a core-shell structure, with its core being lithium-rich spinel lithium manganese oxide, chemically represented as Li. 1+x Mn₂O₄, where x = 0.1 0.3; the core surface is covered with a thickness of 2 A 5 nm thin layer of lithium aluminum oxide (LiAlO2) or aluminum oxide (Al2O3); the charge / discharge potential range of the lithium-rich spinel lithium manganese oxide is 3.0 nm. 4.3V, which matches the charge and discharge range of the high-nickel ternary cathode material, has reversible lithium insertion / extraction capability, and is used to dynamically compensate for the active lithium loss of the ternary composite cathode system throughout the entire cycle.
2. The ternary composite cathode system according to claim 1, characterized in that, Based on the total mass percentage of the ternary composite cathode system, the content of the high-nickel ternary cathode material is 92%. 96%, and the content of the recyclable lithium supplement additive is 1%. 5%, the content of the conductive agent is 1.5%. 2.5%, the content of the adhesive is 1.5%. 2.5%.
3. The ternary composite cathode system according to claim 2, characterized in that, The content of the recyclable lithium replenishment additive is 2%. 3%.
4. The ternary composite cathode system according to claim 1, characterized in that, The high-nickel ternary cathode material is a single-crystal NCM 7-series, 8-series, or 9-series ternary material; the conductive agent is one or more combinations of conductive carbon black, carbon nanotubes, and graphene; and the binder is polyvinylidene fluoride.
5. The ternary composite cathode system according to claim 1, characterized in that, The material of the thin layer is lithium aluminum oxide (LiAlO2), and x = 0.2 in the lithium-rich spinel lithium manganese oxide.
6. A method for preparing a ternary composite cathode system as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Preparation of coated recyclable lithium replenishment additive: lithium-rich spinel Li was synthesized by high-temperature solid-state method. 1+x The Mn2O4 substrate is coated with the 2O4 material via liquid phase coating or atomic layer deposition. The recyclable lithium replenishing additive is obtained by sintering, crushing, and sieving a 5nm lithium aluminum oxide LiAlO2 or aluminum oxide Al2O3 coating layer. (2) Pre-dispersion treatment: The recyclable lithium additive and a portion of the conductive agent are added to NMP solvent at a mass ratio of 1:1 and stirred at high speed for 30 minutes. 60 minutes to prepare a uniform pre-dispersed slurry; (3) Positive electrode slurry preparation: Add the remaining conductive agent, the high-nickel ternary positive electrode material, and the PVDF binder to the pre-dispersed slurry, and stir under low-speed vacuum for 2 hours. After 4 hours, adjust the slurry solids content to 65%. 75%; (4) Coating and molding: The positive electrode slurry obtained in step (3) is coated on the aluminum foil current collector, and after being dried in a segmented gradient, it is cold-pressed to the designed compaction density to obtain a composite positive electrode sheet.
7. The preparation method according to claim 6, characterized in that, The high-speed stirring speed in step (2) is 2000. 3000rpm, the low-speed vacuum stirring speed in step (3) is 800rpm, and the stirring temperature is room temperature.
8. A lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive electrode comprises the ternary composite positive electrode system with recyclable lithium replenishment as described in any one of claims 1-5; The electrolyte is a system of carbonate mixed solvent and lithium hexafluorophosphate, and 1% of lithium salt is added to the electrolyte. 2% fluoroethylene carbonate (FEC) and 0.5% 1% borate ester film-forming additives; The FEC and borate ester film-forming additives are used to form a dense and stable SEI film on the negative electrode to reduce the basic consumption of active lithium from the source, and form a two-way synergistic effect of "reducing loss + replenishing reserves" with the recyclable lithium replenishment additive.
9. The lithium-ion battery according to claim 8, characterized in that, The negative electrode sheet includes an artificial graphite negative electrode or a silicon-carbon negative electrode; the separator is a polyolefin separator.
10. The lithium-ion battery according to claim 8, characterized in that, The borate film-forming additive is tripropyl borate.
Citation Information
Patent Citations
A lithium supplement additive, its preparation method, and a lithium-ion battery
CN111193019B
Preparation method and application of anode lithium supplement additive
CN115133018A
Lithium supplement additive, preparation method and battery containing lithium supplement additive
CN121307032A